Students’ Perceptions of SMA Negeri 1 Toapaya Toward Gadgets in the Biology Learning Process - Oktaviani, Elisa; Miranda, Miranda; Marni, Marni; Putri, Hermilah; Amani, Ruhil; Natasea, Seren; Fernando, Adam; Wahyuni, Sri; Martina, Martina (Biology and Education Journal, 2026)
Digital media is any type of electronic media that can be stored, accessed, and changed by a computer. One of the Digital Media that is often used today is gadgets. Gadgets are small electronic devices that can be carried to find information or communicate with others. In this era of globalization, gadgets are also difficult to use in learning. The times allow the implementation of technology in the world of education. At SMA Negeri 1 Toapaya, one of them is driving school and has implemented an independent curriculum so that access to technology is needed in it. Therefore, especially in learning Biology. This study uses descriptive methods with quantitative data analysis techniques in the form of a questionnaire instrument covering 8 indicators. The results of this study found that SMA Negeri 1 Toapaya students tend to prefer learning using gadgets, because with gadgets they can access wider information so as to increase their understanding and confidence in learning.